Augmenting Ground Water Recharge Through Surface Drains - Singh, Satvinder; Kaushal, M P; Singh, Satwinder (Journal of Agricultural Engineering, 2009)
An existing mathematical model correlating runoff with recharge rate in a drain was used to determine the recharge rate through a surface drain. Two flow conditions were considered namely, free flow and detained flow. Detained flow conditions were made through a series of checks along the drain. Thirty years of rainfall values in the monsoon period was given as input to the model to yield runoff. Recharge in the Raipur Link drain, Distt. Ludhiana. Punjab occurring due to runoff was determined. On an average, recharge caused by the runoff in the drain was 3% of the rainfall when the flow was detained. The highest value was 7.35% for a single event. The volume of water recharged under detained flow was 4.86 times of that under free flow condition.